Delivering perioperative care and education in Kenya. Issue 5 (May 2019) - Rich, Chloe
The purpose of the Hilda Mears' Volunteer Award is to help members share their knowledge and skills with other voluntary organisations who facilitate direct patient care to overseas patients where access to free quality healthcare is not available. Two awards are presented each year by AfPP at the annual Residential Conference in August.